Dichloro Butenediamides as irreversible site‐selective protein conjugation reagent - Laserna, Victor (2021)
© 2021 The Authors. Angewandte Chemie International Edition published by Wiley-VCH GmbH. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.